Eggplant anthocyanin-mediated zinc oxide nanoparticles incorporated multifunctional film (hydroxypropyl methylcellulose/chitosan) for Caspian Sea white fish (kutum Rutilus frisii) packaging - Mahsa Salehi; Amir Shakerian; Zohreh Mashak; Ebrahim Rahimi (Future Foods)
Multifunctional films were fabricated from hydroxypropyl methylcellulose (HPMC), chitosan (CH), eggplant peel anthocyanin (ACNs), and zinc oxide nanoparticles (ZnONPs) biosynthesized with caps’ extract of eggplant (1, 3, 5 %) for application as Caspian Sea white (kutum Rutilus frisii) packaging. The extraction efficiency from eggplant caps was 3.73%. Dynamic light scattering results showed a uniform distribution of ZnO with a polydispersity index of 0.332. Fourier-transform infrared spectroscopy and X-ray diffraction results confirmed the presence of CH, ACNs, and ZnONPs in the film matrix. The incorporation of CH, ACNs, and ZnONPs into the HPMC matrix increased the moisture content, water vapor, and oxygen permeability, increasing tensile strength. Increasing the level of ZnONPs in the polymer matrix increased the migration rate. The fabricated films exhibited a clear color change from red in acidic conditions to yellow in alkaline conditions, depending on the pH. The HPMC-CH-ACNs-3%ZnONPs smart films effectively extended the shelf life of whitefish fillets by reducing mesophilic bacteria growth (8.16-7.67 log CFU/g) and total volatile basic nitrogen values (11.76±0.56 mgN2/kg), increasing a*color (redness) indices within 7 days of storage time.